Study of Social and Economic Status of Disabled Persons with Special Reference to District Bijnor - Nooreen (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The study examines the socio-economic conditions of persons with disabilities in Bijnor district of Uttar Pradesh, focusing on their challenges in accessing higher education. The data has been collected from Premdham Ashram, Najibabad, set up in 2009 to help orphaned disabled persons, destitute and terminally ill people. Premdham provides essential services including food, shelter, clothing, and comprehensive rehabilitation programs for individuals to integrate into society. Disability, defined as a range in physical, mental or cognitive abilities, affects 2.21% of India's population. In Bijnor, a large number of persons with disabilities are facing socio-economic barriers, which hamper their education and employment opportunities. The findings showed that the socio-economic status of individuals with mobility disability is strongly related to the educational achievement and occupation of the breadwinner of the family. The heads of most households with disabled members in the area are educated up to the matriculation level, but are engaged in unskilled labor. The socio-economic distribution shows almost equal representation in the upper-middle, lower-middle and upper-lower classes. Despite some progress in education and employment, these families continue to struggle with poverty, limited access, and unequal opportunities. The study underscores the need for targeted policies to improve accessibility and socio-economic conditions of persons with disabilities, enabling their participation in higher education and skilled employment opportunities.